Investigating Indonesian pre-service English teachers: perceptions and motivations to enter the teaching profession - Aplonia Nelci Ke Lomi; Concilianus Laos Mbato (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Teaching is one of the fundamental professions in society. Pre-service English teachers’ perceptions and motivations may significantly influence their career decision-making to enter the profession. This study aimed to investigate pre-service English teachers’ perceptions and motivations to enter the teaching profession. It employed mixed-method research with questionnaire and interview as the instruments to collect data. The respondents were 44 pre-service English teachers from an English Teacher Education Department of a well-known university, in East Nusa Tenggara Province, Indonesia. Results showed that the students had various perceptions regarding the teaching profession and most of them were altruistically motivated to be teachers in the future. The current study offers two important implications. First, since perceptions and motivations to enter the teaching profession are not fixed and may be influenced by the students’ family, environment, and study program, building positive perceptions and motivations should be an integrated element of the teacher education curriculum. Second, graduating students need strong support from the family, environment, and the government to maintain positive perceptions and motivations about the profession.